Heterogeneous photo-Fenton process mediated by Sn-substituted goethites with altered OH-surface density - Larralde, Ana Laura (2019)
Heterogeneous photo-Fenton process using several pure- and Sn-incorporated goethites was investigated for the decolourisation of methyl orange (MO). The used goethites presented a partial Sn(IV)-for-Fe(III)substitution. Among other properties variations, this partial replacement provoked changes in the OH-surface density (OSD)of the oxo(hydr)oxide. The effect of Sn-for-Fe substitution on the MO decolourisation was investigated by analysing several processes that might occur when combining H2O2, UV–vis irradiation and the iron oxides, with the dye. The best performance was achieved when a slight substitution of Sn-for-Fe was used, indicating that tin contributes indirectly to the decolourisation by increasing the OSD and assisting the reduction of Fe(III)→ Fe(II)through an intermediate between tin and H2O2 (SnOOH). The proposed mechanism for the MO decolourisation using the Sn-substituted goethite involves an indirect pathway not previously reported for the photo-Fenton process.